Social and Solidarity Economy. The Case of an Urban Consumption Co-operative in Greece - Petropoulou, Eugenia A. (PARTECIPAZIONE E CONFLITTO, 2018)
The apparent ubiquity of alternative – to the dominant economic model – economies, after the 2008 multidimensional crisis across the world, fuelled claims about a new style of mobilisation emerg-ing in Greece. It is the outcome of the evolution of the Greek anti-austerity movement and community-based experiences, consolidated to form new affiliations of collective initiatives and practices. Analysing original qualitative data derived from a case study of a Greek Urban Consumer Co-operative, this article engages with the debate of Social and Solidarity Economy. The research highlights the capacity of a Greek Urban Consumer Co-operative through sustainable consumption patterns to utilise local-traditional re-sources in order to empower local communities in times of crisis. Theoretically, this urban consumer co-operative generates new insights into the nature and meanings of a more sustainable and just economy, by changing the way it buys and sells food and other goods. From a policy and practice perspective, the paper raises the need for regional development strategies that capture the ’alternativeness’ of these iso-lated initiatives, whose practices promote ethical, as well as environmental criteria and considerations in times of global economic crisis.